Design parameters for retrofitted masonry to timber connections - Moreira, Susana Maria Trindade (2014)
Proper structural connections play an important role in ensuring seismic loads distribution and developing global damage mechanisms of structures. In unreinforced masonry buildings, positive connections between masonry walls and timber floors or walls through the use of anchors can prevent the occurrence of out-of-plane mechanisms and promote box-behavior. Therefore, this paper aims at developing structural modeling parameters and acceptance criteria that allow the design of anchored connections for historical URM buildings from the late 19th century, in Portugal. An experimental campaign was carried out, where quasi-static monotonic and cyclic pullout tests were carried out on strengthened wall-to-floor connections and wall-to-timber framed connections. Both retrofitting solutions rely on anchoring the timber floor or framed wall to the masonry wall, through the use of steel tie-rods with anchor plates or injection anchors, respectively. From these tests, it was possible to study their hysteretic behavior and failure modes, as well as quantify the maximum pullout capacity, the ductility, the energy dissipation and other parameters. This information was the base to establish multilinear backbone curves and design parameters for each type of behavior observed experimentally. Experiments performed in strengthened wall-to-floor connections with two wall thicknesses (0,4 m and 0,6 m) and in wall-to-timber framed wall connections with injection anchors at the top of a wall demonstrated high ductility and were classified as deformation-controlled actions. Being governed by shear slip enabled them to obtain large displacements with small strength loss. For the injection anchors, the applicability of strength prediction formulas based on different failure models was studied. The adapted ACI 530-05 model for cone breakout was the one that better predicted the experimental values obtained for the tests performed at the top of the wall. Bond failure models were highly dependent on the bond strength of the grout/masonry interface and provided reasonable approximation to the results. Further use requires the determination of accurate grout/masonry interface bond strength. Future work includes simplification of backbone curves and development of hysteretic rules.